2000
DOI: 10.1007/bf03162148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of charge transfer state on the exchange interaction of radical-triplet encounter pairs

Abstract: Chemically induced dynamic electron polarization (CIDEP) of galvinoxyl was measured in various excited molecule-galvinoxyl systems prepared by laser photolysis. Most of the systems examined showed net emission CIDEP, which is well explained by the quartet precursor radical-triplet pair mechanism with exchange interaction, J, of negative sign (quartet is higher than doublet). Several systems with molecules such as naphthalene, quinoxaline, biphenyl and triphenylene, however, showed net absorption CIDEP. Time pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The discussions mentioned above are based on RT pairs with the negative J value. If the pair shows the positive J value, the signal sign becomes opposite to that in the pair with the negative J value [16,17]. This relation is summarized in Table 1.…”
Section: Sign Rule For the Cidepmentioning
confidence: 83%
See 2 more Smart Citations
“…The discussions mentioned above are based on RT pairs with the negative J value. If the pair shows the positive J value, the signal sign becomes opposite to that in the pair with the negative J value [16,17]. This relation is summarized in Table 1.…”
Section: Sign Rule For the Cidepmentioning
confidence: 83%
“…The former is for the CIDEP created in any radical-triplet (RT) pairs, while the latter is for the CIDEP in radical and spin-polarized triplet systems. The pattern of CIDEP by RTPM in excited state quenching is certainly related to the electron spin dynamics of the quenching process, and efforts to analyze the CIDEP pattem have been made to clarify many details of the potential surfaces of an RT pair and the spin dynamics [9][10][11][12][13][14][15][16][17]. One of the most widely studied subjects on the basis of CIDEP analyses in excited state quenching is the enhanced intersystem crossing (ISC) of both S 1 and T~ molecules promoted by the effects of free radicals.…”
Section: A Kawaimentioning
confidence: 99%
See 1 more Smart Citation
“…A negative polarization (A) is observed in the few cases where the radical and the triplet are rigidly linked in a proper position ensuring zero overlap, 20,21 or when in the RTP there is a consistent contribution of charge transfer from the radical to the triplet partner. 22 As for the multiplet effect, emission at low field and absorp-…”
Section: Cidep Generation By Rtpmmentioning
confidence: 99%
“…Usually J is negative, but recent investigations showed that J is positive in the pairs of some triplet molecules with galvinoxy radical [63,64], where an intermolecular CT state interacts with the RTP state only among the doublet spin states. When the blue shift caused by this effect is larger than the energy separation of the doublet and quartet states by the exchange interaction, the sign of the 3"0 value turns over to be positive.…”
Section: Cidep Workmentioning
confidence: 99%